Amorphous InGaZnO and metal oxide semiconductor devices: an overview and current status. Issue 40 (2nd October 2019) - Troughton, Joe; Atkinson, Del
Abstract : This review covers the history, development, and state of the art, of metal oxide-based electronics, with particularly focus of indium-gallium-zinc-oxide. Abstract : The past 20 years has witnessed a rapid expansion of applications using metal oxide semiconductor devices that ranges from displays technology, to clothing and packaging. Details of these technological applications have been the subject of technical reviews, but the materials and specifically the metal oxide devices have not been coherent reviewed. This work brings together a wide range of information to present an overview of the history and development of metal oxide devices, from their earliest inception to the most recent advances. This begins with a discussion of the first developments of metal oxides and their applications, and the earliest realisations of metal oxide semiconducting devices and moves on to a discussion of the factors that need to be considered in designing metal oxide semiconducting devices, including; material choice, deposition methods and device structure. This is followed by an in-depth review of the effects of material defects and concludes with a review of the current state of applications based on metal oxide semiconductors.